Protecting Sensitive Data in Salesforce – A Multi-Layered Security Approach - Sadaf Jahan; Faiyaz Ahmad; Mohd Haroon (International Journal of Engineering and Management Research, 2023)
Data security is a paramount concern for organizations across various industries, particularly when it comes to customer relationship management (CRM) platforms like Salesforce. As businesses increasingly rely on Salesforce for managing critical customer data, it is crucial to understand the security measures and best practices necessary to protect sensitive information from unauthorized access, breaches, and data leaks. This research paper provides a comprehensive review of data security measures and best practices specifically tailored for Salesforce implementations. The objective is to equip organizations and Salesforce administrators with the knowledge and tools needed to establish robust security protocols and mitigate potential risks. The paper examines the fundamental security features provided by Salesforce, including user authentication, access controls, and data encryption. It explores advanced security capabilities such as identity management, single sign-on (SSO), and multi-factor authentication (MFA), highlighting their role in enhancing data security and user access management. Additionally, the research delves into the significance of data governance and data classification in maintaining data integrity and privacy. It discusses the implementation of role-based access control (RBAC), data sharing rules, and object-level permissions to ensure that data is accessible only to authorized individuals. Furthermore, the paper explores best practices for securing data during transit and at rest, covering topics such as Secure Sockets Layer (SSL) encryption, data encryption at rest, and data backup strategies. It also addresses the importance of regularly monitoring and auditing user activity, employing security monitoring tools, and conducting vulnerability assessments and penetration testing. By comprehensively reviewing the security measures and best practices in Salesforce, this research paper aims to serve as a valuable resource for organizations seeking to fortify their data security posture, protect customer information, and maintain compliance with data protection regulations.